PEMETAAN BAHAYA GEMPA BUMI DAN POTENSI TSU-NAMI DI BALI BERDASARKAN NILAI SEISMISITAS - Baskara, Bayu; Sukarasa, I Ketut; Septiadhi, Ardhianto (BULETIN FISIKA; Vol 18 No 1 (2017): BULETIN FISIKA, 2017)
Bali is one of the areas prone to earthquake and tsunami as being at the junction of two plates, namely the Eurasian plate and the Indo-Australian plate is located in the south of Bali and back arc trust zones are located in the North of Bali. We need research on the potential dangers of earthquakes and tsunami in Bali are based on the value of seismicity which is interpreted by the value of b and a. This study uses earthquake data on the coordinates 6?-11? SLand 114?-116? EL with 339 data that was processed using Zmap in order to obtain the value of b at 1.57 ± 0.008 and the value of a is 10.6 and maximum magnitude of 7.1 Mw. From mapping the values ??of b and a known area that has the highest value of b and a lies in the sea area to the south of Bali, Karangasem and Buleleng to the northern region of Bali. Furthermore, for mapping the tsunami in Bali using the TOAST application obtained tsunami prone areas of Bali, Kuta Beach, East Buleleng and Karangasem.